Human dignity in international law / Ginevra Le Moli. - Le Moli, Ginevra (ASIL studies in international legal theory., 2021)
Over the past two centuries, the concept of human dignity has moved from the fringes to the centre of the international legal system. This book is the first detailed historical, theoretical and legal investigation of human dignity as a normative value, the intellectual sources that shaped its legal recognition, and the main legal instruments used to give it expression in international law. Ginevra Le Moli addresses the broad historical and philosophical developments relating to the legal expression of dignity and the doctrinal geography of human dignity in international law, with a focus on international humanitarian law, international human rights law and international criminal law. The book fills a major lacuna in the literature by providing a comprehensive account of dignity within international law that draws on an extensive documentary and archival basis and a vast body of decisions of international judicial and quasi-judicial bodies.